Clinical characteristics and gene analysis of SYNGAP1-related epilepsy in children - Tian, X J (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2021)
Objective: To summarize the clinical characteristics of SYNGAP1-related epilepsy in children. Methods: Data of 13 patients with SYNGAP1 gene variants diagnosed with epilepsy at Department of Neurology, Beijing Children's Hospital were collected retrospectively from March 2017 to October 2020 and the patients were followed up. The clinical features, electroencephalogram(EEG), brain imaging, gene results and treatment were summarized. Results: Twelve patients were followed up successfully among the 13 patients with SYNGAP1 variants. The last follow-up age was 5 years and 7 months (3 years and 1 month to 9 years).The onset age of seizures was 2 years (4 months to 3 years). Seizure types included eyelid myoclonia with or without absence (9 cases), myoclonic seizure (5 cases), atypical absence (4 cases), suspicious atonic seizures(4 cases),unclassified fall attack (6 cases), and the frequency of seizures varied from several times to more than 100 times per day. Four cases had the mimic phenotype of myoclonic astatic epilepsy. The seizures of 10 cases could be triggered by eating (5 cases), emotion (5 cases), fever (3 cases), voice (2 cases), fatigue (2 cases), etc. Electroencephalography (10 cases) showed interictal generalized or focal epileptiform discharges (9 cases), and atypical aphasia (4 cases), myoclonic seizure (2 cases) and eyelid myoclonic seizure (1 case) were monitored. Of the 12 cases, 9 were added with valproate, all of which were effective (the frequency of seizures reduced>50%). Five cases received combined levetiracetam, in 3 the treatments were effective. To last follow-up, 3 cases were seizure free from 6 months to 1 year and 1 month, but the remaining 7 cases still had seizures, one or several times per day. All 13 cases had developmental retardation (speech ability impaired mostly), 2 cases were severe, 10 cases were moderate, 1 case was mild. The SYNGAP1 gene variants of 13 patients were all de novo, including 12 variants. Among them, 4 were frameshift variants, 4 were nonsense variants, 2 were missense variants and 2 were splice site variants. Conclusions: Patients with SYNGAP1-related epilepsy have an early onset age and many seizure types. The main seizure type is eyelid myoclonia with or without absence, and other seizure types include myoclonic seizure, atypical absence, unclassified fall attack, etc. Valproate is effective in most patients, but seizures in some patients might be intractable. Most patients have developmental delay (mainly moderate and severe), speech ability impaired mostly